THE EFFECT OF FIRM PERFORMANCE ON CSR PERFORMANCE MODERATE BY THE PROPORTION OF INDEPENDENT COMMISSIONERS IN NON- FINANCIAL COMPANIES LISTED ON THE IDX FOR 2016-2020 PERIOD - Surbakti, Manuel Aristo; Devi Maya Sofa; Petrus Fraidylegif Putra Djatu (Ecopreneur.12, 2024)
Study aims to see effect between the company performance and CSR performance in non financial companies list onIDX for period 2016 - 2020. Using purposive sampling, 1,940 research samples were obtained. Researchers useregression panel data. Result showed company performance was not significantly related to CSR performance.Company has a social responsibility to society that good and bad performance of the company does not affect CSRperformance. Result also show proportion of independent boards of commissioner could not strengthen influence ofcompany performance to CSR.